(untitled) (IAHS Medical Journal, 2022)
Background: Estimation of stature from index finger length in adult Chakma males and females and also to observe gender difference was the main purpose of this study. Materials and methods: It was a cross-sectional analytical study conducted over 104 adult healthy Chakma males and females (52 males and 52 females) residents of Chattogram Hill Tracts area in the year 2016 and 2017. Subject selection was done by convenience sampling technique and stature and index finger length were measured and data were documented in SPSS version 19. Results: A highly significant (p<0.001) gender difference was found in index fingers length. Mean Multiplication Factor (M.F.) to estimate stature in males was 25.1239 and 25.1149 for right and left index finger respectively and in female was 25.2505 and 25.2135 for right and left index finger respectively. A highly significant (p<0.001) positive correlation was found between stature and right index finger length 0.571 and left index finger length 0.576 in Chakma males. The stature and right index finger length 0.630 and left index finger length 0.679 in Chakma females respectively. Conclusion: This study found multiplication factors for right and left index finger length to estimate stature in a correct way and found a linear correlation between stature and index fingers length. There was significant gender difference present between index fingers length in between adult Chakma males and females. IAHS Medical Journal Vol 5(1), June 2022; 22-26